2017
DOI: 10.1149/2.1441704jes
|View full text |Cite
|
Sign up to set email alerts
|

Critical Review—Identifying Critical Gaps for Polymer Electrolyte Water Electrolysis Development

Abstract: Although polymer electrolyte water electrolyzers (PEWEs) have been used in small-scale (kW to tens of kW range) applications for several decades, PEWE technology for hydrogen production in energy applications (power-to-gas, power-to-fuel, etc.) requires significant improvements in the technology to address the challenges associated with cost, performance and durability. Systems with power of hundreds of kW or even MWs, corresponding to hydrogen production rates of around 10 to 20 kg/h, have started to appear i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
347
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 398 publications
(366 citation statements)
references
References 112 publications
3
347
0
4
Order By: Relevance
“…One explanation is to connect the deviation from what the Tafel equation predicts at higher currents to mass transport phenomena [28]. However, in this work mass transport problems are excluded due to high over-stoichiometry, interdigitated feed water channels, a small cell geometry, and a high anode PTL porosity [56]. Additionally, no evidence for mass transport problems were found in the recorded IV curves or impedance spectra.…”
Section: Tafel Plot Analysismentioning
confidence: 90%
“…One explanation is to connect the deviation from what the Tafel equation predicts at higher currents to mass transport phenomena [28]. However, in this work mass transport problems are excluded due to high over-stoichiometry, interdigitated feed water channels, a small cell geometry, and a high anode PTL porosity [56]. Additionally, no evidence for mass transport problems were found in the recorded IV curves or impedance spectra.…”
Section: Tafel Plot Analysismentioning
confidence: 90%
“…7 This two-phase flow was visualized by visible light, neutron and X-ray imaging with focus of the PTL/flowfield interface and the flow regime in the channels. [20][21][22][23] Based on operando in-plane neutron radiography data, Seweryn et al 24 reported a gas/water ratio in the PTL independent of current density, verified up to 2.5 A · cm −2 .…”
Section: F974mentioning
confidence: 99%
“…Ohmic and kinetic overpotentials, related to the movement of protons in the polymer electrolyte and the finite rates of the electrochemical reactions are reasonably well understood for PEWE. [6][7][8] In most cases, at least at current densities above about 1 A · cm −2 , losses in addition to ohmic and kinetic sources are observed and related to mass transport resistances in the porous structures of the catalyst and porous transport layers (PTLs), though their nature and origin in PEWE are not well understood.6 Nevertheless, as long as a sufficient water supply is guaranteed, no transport limitations occur in the form of a turning point in the current/voltage characteristics (i/E-curves), as demonstrated by Lewinski et al 9 up to 19 A · cm −2 . In polymer electrolyte fuel cells (PEFC), a technology similar to PEWE, the effect of mass transport in the micro-porous structures of the electrodes and PTLs on the performance of the cells is reasonably well studied.…”
mentioning
confidence: 99%
“…Hence, a growing concern in the context of large-scale PEM water electrolysis applications is the availability of Ir, which is one of the rarest materials on earth with an estimated annual production of only ≈4 tons. 4 In a recent study by Babic et al, the authors estimate that if 25% of the annually produced Ir were to be used for PEM water electrolysis and considering that current PEM water electrolyzers require ≈0.5 g Ir kW −1 , the annual PEM water electrolyzer installation would be limited to 2 GW/year. 4 This currently estimated maximum Ir-supply limited annual PEM water electrolyzer installation capacity may be compared to the water electrolysis capacity which would be needed, for example, if a large fraction of the currently used fossil fuels in the transportation sector were to be replaced by hydrogen.…”
mentioning
confidence: 99%